Pola Kandang Tertutup Dua Lantai pada Broiler di Edi Sujarwo Farm Kabupaten Lampung Tengah - C A Patria (PETERPAN (Jurnal Peternakan Terapan), 2022)
The use of closed-house cages is one of the technological innovation efforts to deal with the adverse effect of environmental conditions or changing weather. Setting environmental conditions will make broilers feel comfortable. The type of cage with a double deck system in a closed house will minimize the limited land area. In addition, the implementation of the closed-house double deck is expected to have a positive impact on increasing broiler production. This study aims to determine the pattern of Edi Sujarwo Farm’s closed-house double deck. The method used is descriptive. Data were collected using primary and secondary data. The result showed that Edi Sujarwo Farm’s Closed House Double Deck cage uses a cage construction that is safe for broilers and workers. The cage leads from east to west with a temperature of 260C - 320C with a humidity of 70%. The feeders are baby chick and hanging feeders. The watery system used is a nipple drinker. Other equipment used in the form of temptation, generator, curtain, and high-pressure sprayer. The ground floor and the first level consist of 6 blowers on floor units. Cooling pad used (150 cm x 60 cm) with a thickness of 15 cm. Biosecurity and sanitation programs are carried out before and after harvest.